CELLER TIL SALG: KUNSTNERISKE FORTOLKNINGER AF VÆVSØKONOMIER - Leth-Espensen, Pernille (K&K - Kultur og Klasse, 2018)
CELLS FOR SALE: ARTISTIC INTERPRETATIONS OF TISSUE ECONOMIES An extensive circulation of human tissue is taking place in our society today: blood, organs, reproductive tissue (eggs and semen), and cell lines. This circulation and commercialisation is thematised by a range of contemporary artists, who creates artworks with cell and tissue culture technologies. The artist Alicia King has bought Hs 53.T cells from the cell bank ATCC (The American Type Culture Collection) and created a monument around this cell line. These cells originate from a 13-year old Afro-American girl, and the cell sample was taken in 1969. The artist Chrissy Conant instead uses her own tissue. She has ’harvested’ 12 of her own eggs at a fertility clinic, preserved them in glass jars with a lid inspired by caviar packaging, and put them for sale at 250.000. In the article it is argued that the artworks address the commercial relations in cell and tissue culture technologies by making visible technologies or processes that are unknown to the broader public or through a strategy of exaggeration.